Development of a combined flash and binary geothermal system integrated with hydrogen production for blending into natural gas in daily applications - Ozturk, Merve; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
This paper concerns a novel integrated system for geothermal-based power and hydrogen generation and blending of hydrogen into natural gas to feed household devices, such as gas stove and combi boiler. The system includes a combined flash and binary geothermal subsystem, an alkaline electrolyzer, a blending unit and a combustion reactor. The design and modelling of the proposed system are conducted with Aspen Plus software. The overall energy and exergy efficiencies of the investigated system are found to be 46.8% and 77.9%, respectively. The highest exergy efficiency belongs to January as 86.63% when the average ambient temperature is 5.8 degrees C, while the lowest exergy efficiency belongs to July as 76.98% when the average ambient temperature is 27.2 degrees C in Denizli, Turkey. The hydrogen fraction into natural gas is changed from 0% to 20% and analysed the combustion of the blend. The results show that syngas composition has higher oxygen output rate and lower carbon dioxide, steam and heat release rates with higher hydrogen addition.
Keywords: Geothermal energy; Hydrogen; Efficiency; Electrolyzer; Exergy; Natural gas; ORGANIC RANKINE-CYCLE; THERMOECONOMIC ANALYSIS; POWER-PLANT; ENERGY; NETWORKS; DRIVEN; WATER; Thermodynamics; Energy & Fuels; Mechanics